An analysis of the independent trade unions in South Africa in the 1970s - Maree, Johannes Gerhardus Bester (Department of Sociology, 2023)
The thesis is an historical and sociological study of the independent trade unions in South Africa in the 1970s. Several research methods were used: participant and non-participant observation, primary and secondary source, and open-ended interviews. In addition, shown to the unions for correction of clarification of issues. material, structured earlier drafts were factual errors and the findings of the thesis are as follows: historically, the independent unions went through two stages in the 1970s. During the first stage they struggled for survival against capital and the state, which opposed their very existence. At the end of 1976 their future hung in the balance because of political turmoil, economic recession, and state repression. But they survived and in the second stage they fought to gain formal recognition at a limited number of companies. Sociologically, the thesis focusses on two major themes: the efforts of the independent unions to be democratic organisations and their strategies to acquire power. A central finding is that the independent unions strove to build up their strength by organising democratically at the workplace. Certain strategies in organising and tactics in industrial disputes were more successful than others in helping the unions build up their strength. The unions went through a democratisation process that entailed three phases: the creation of democratic structures in the unions, developing workers' capacities to take control of the structures, and the emergence of representative and accountable worker leadership. While this process had not been completed by the end of the period under consideration, the strong influence initially exercised by intellectual leaders was reduced considerably. The empirical findings of the thesis are used to evaluate the appropriateness of relevant sociological theories of trade unions and related issues. They are frequently found to be inappropriate , being based on conditions very different from those that faced the independent unions. Finally , it is concluded that the democratic form of organisation adopted by the independent unions in the 1970s had a definite political significance which started emerging in the 1980s.